Advocacy and communication strategies for increasing engagement of sectors and stakeholders. - Malla, Savita. (Tufts University. Tisch Library., 2016)
Ms. Malla's presentation provides a clear perspective on how the government views nutrition action through policy commitments, and Ms. Malla brings in her own angle of how media, communication, and advocacy can enhance that. Delivered on Day 1 of the 2016 NIL Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy